Question

If tan x = 2b/(a – c) (a  c), y = a cos2 x + 2b sin x cos x + c sin2 c and z = a sin2 x – 2b sin x cos x + c cos2 x, then

Solution

Correct option is

y + z = a +  and y – z = a – c

Adding the expression for y and z, we get

y + z = a (cos2x + sin2 x) + c (sin2 x + cos2 x) = a + c

And subtracting them

                                                                                 

            

            

            

            

            

 

SIMILAR QUESTIONS

Q1

 

Q2
Q5
Q6

Which of the following statement is correct

Q7

 then the value of tan α tan 2α tan 3α….tan(2n-1)α is equal to

Q8

The number of solution of the equation

  is/are

   

Q9
Q10